(untitled) (The Research of Medical Science Review, 2024)
Objective: The objective of this research work was to find out the altered levels of lipid profile in thyroid patients in comparison to healthy subjects of Khairpur city Sindh. Methodology: The study was designed to compare lipid profile of healthy subjects and thyroid patients of Khairpur city. The study was carried out from August 2019 to October 2019. The thyroid patients and healthy subjects including males and females aged up to 25 and above 25 years were studied. By applying random sampling methodology a total of 122 blood samples from thyroid patients and healthy subjects were collected from Kausar Hospital Khairpur and Civil Hospital Khairpur. The serum samples were analyzed for total cholesterol, very low density lipoproteins (VLDL), low density lipoproteins (LDL), high density lipoproteins (HDL) and triglycerides (TGs) to evaluate if any alteration in their levels due to altered levels of Thyroid hormones. The data was analyzed by using IBM® SPSS® Statistics21.0 Software. Results: 122 subjects including 46 males (37.7%) males and 76 (62%) females were studied. According to this study highest frequency was found of females. The mean total cholesterol, low density lipoprotein, cholesterol and triglycerides were higher in hypothyroid cases than healthy subjects. It was observed that the mean values for various components of lipid profile were significantly greater in hypothyroid cases as compared to healthy subjects. Hyperthyroid condition does not show any statistical significance with lipid profile. Conclusion: This study concludes that hypothyroidism has adverse impact on lipid profile level, as the levels of triglycerides; very low density lipoproteins and cholesterol were found increased in hypothyroid patients.